PENGEMBANGAN MODUL BERBASIS KONSTRUKTIVISME PADA MATERI SISTEM PERIODIK UNSUR KELAS X SMA/MA SEDERAJAT - Ilyana, Ilyana; Azmi, Johni; Holiwarni, Betty (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This study aims to develop constructivism-based modules on periodic systems pf elements that are valid and practical . This development research uses a 4-D model that has 4 stages, namely, Define, Design, Develop and Disseminate. To produce a valid module, the module validity test is carried out which includes four aspects of assessment, namely the characteristics of the module, aspects of quality elements, linguistic aspects and aspects of presentation. To see the practicality of the module a limited test was conducted at SMAN 6 Pekanbaru and SMAN 12 Pekanbaru. The results of the study that have been validated by 3 validators state that the percentage is 91.06%. The results of the test questionnaire were limited to 30 students, 90.54% and the results of the responses from 2 chemistry teachers were 90.38%. Based on the results of limited validation and testing, constructivism-based modules on periodic system material elements are declared valid and practical.Keywords: Module, Constructivism, Periodic System of Elements